Decidual macrophages derived NO downregulates PD-L1 in trophoblasts leading to decreased Treg cells in recurrent miscarriage - Zhang, Yonghong; Wang, Huiyan; Qiu, Panpan; Jiang, Jingwen; Wu, Xuhong; Mei, Jie; Sun, Haixiang (Frontiers in Immunology, 2023)
Placental trophoblasts contribute to Treg function via the programmed cell death-1 (PD-1)/PD-1 ligand 1(PD-L1) pathway during normal pregnancy. Decreased expression of PD-L1 in trophoblasts was closely associated with regulatory T (Treg) deficiency in the development of pregnancy failure. Thus, targeting PD-L1 might be a novel therapy to prevent pregnancy loss. However, the mechanisms for modulating the expression of PD-L1 in trophoblasts is an enigma. Yin And Yang 1 Protein (YY1), is a widely distributed transcription factor. In this study, decreased expression of YY1 and PD-L1 in trophoblasts and lower proportion of decidual Treg cells were observed in patients with recurrent miscarriages (RM). The modulatory effects of YY1 on PD-L1 were determined using HTR-8 cells with siYY1 transfection. Knockdown of YY1 contributes to lower expression of YY1 and PD-L1. Soluble PD-L1 in the supernatant from HTR-8 cells was also decreased with siYY1 administration. Furthermore, lower Treg differentiation was observed in the presence of supernatant form HTR-8 cells treated with siYY1. CHIP analysis of human early villous revealed that endogenous YY1 directly occupied the promoter region of the CD274 (PD-L1) gene. Furthermore, we explored the potential modulatory effects of decidual macrophages (DM) derived nitric oxide (NO) on YY1/PD-L1 in trophoblasts. SNAP (the NO donor) administration inhibited YY1 and PD-L1 in HTR-8 cells. Furthermore, Treg differentiation was also inhibited in the presence of supernatant from SNAP treated HTR-8 cells. Moreover, in vivo data showed that decreased expression of YY1 and PD-L1 in trophoblasts and lower percentage of uterine Treg cells, as well as increased fetal loss were observed in the SNAP and mouse M1 macrophages treated pregnant mice. This was the same case for the abortion-prone pregnant mice. Taken together, higher percentage of M1 macrophages or higher level of NO inhibited the expression of YY1 and PD-L1, which may be potentially responsible for the observed pregnancy loss and lower proportion of Treg cells.